COMPARISON OF EFFICACY OF ORAL PROGESTERONE AND MICRONIZED PROGESTERONE PESSARY IN REDUCTION OF INCIDENCE OF SPONTANEOUS PRETERM BIRTHS - Afridi, Nighat; Masood, Umair; Balooch, Salahuddin; Khan, Saifullah; Khan, Shahgul (Journal of Ayub Medical College Abbottabad, 2019)
Background: Preterm births are among the leading causes of fetomaternal mortality and morbidity. Progesterone is routinely used for the treatment of preterm births but scarce data is available that compared the efficacy of oral progesterone (dydrogesterone) with micronized progesterone (cyclogest pessary/rectal) to reduce the incidence of spontaneous preterm births in our local population. Methods: This randomized controlled trial was conducted at Gynaecology and Obstetrics department of Combined Military Hospital Nowshera from June to November 2018. Patients were divided into two groups. Group A was given oral progesterone (10 mg twice daily) while group B was given cyclogest pessary (400 mg daily) per rectal use. Efficacy of both groups was compared applying chi-square test and p-value ‰¤0.05 was considered significant. Results: Total 152 patients were included in study with 1:1 randomization (76 patients in each group). Mean gestational age was 29.6 weeks±1.5SD. Micronized progesterone cyclogest pessary per rectal usage is associated with reduction in preterm C-section, maternal systemic side effects., tocolysis use, NICU admissions, perinatal mortality, intraventricular haemorrhage, oxygen use at 28th day of life and retinopathy of prematurity (p<0.05). An insignificant association between two interventional groups and reason for delivery, antenatal corticosteroids use, birth weight, respiratory distress syndrome, pneumonia, sepsis (p>0.05). Conclusion: Prophylactic micronized progesterone per-rectal use is more effective in reducing preterm birth in patients at high risk of prematurity as compare to oral progesterone (dydrogesterone). Cyclogest pessary 400mg per rectal usage is associated with less maternal and neonatal complications. Keywords: cyclogest pessary (micronized progesterone); Dydrogesterone; Preterm birth